Answer:
(2, - 3 )
Step-by-step explanation:
Given the 2 equations
y = - 3x + 3 → (2)
y = - 9x + 15 → (2)
Substitute y = - 3x + 3 into (2)
- 3x + 3 = - 9x + 15 ( add 9x to both sides )
6x + 3 = 15 ( subtract 3 from both sides )
6x = 12 ( divide both sides by 6 )
x = 2
Substitute x = 2 into either of the 2 equations and solve for y
Substituting into (1)
y = - 3(2) + 3 = - 6 + 3 = - 3
solution is (2, - 3 )
Answer:
See attachment
Step-by-step explanation:
- <em>Remember: height is always perpendicular to the base</em>
<em>See attached for answer</em>
<em />
The answers are 6, 7, 8, and 11.
Hope this helps! :D
Triangle, sum of all 3 angles = 180
so 180 - (99 + 11) = 180 - 110 = 70
answer: the third angle = 70